2012
DOI: 10.1051/0004-6361/201219056
|View full text |Cite
|
Sign up to set email alerts
|

Radio spectra and polarisation properties of a bright sample of radio-loud broad absorption line quasars

Abstract: Context. The origin of broad-absorption-line quasi-stellar objects (BAL QSOs) remains unclear. Accounting for ∼20% of the QSO population, these objects have broad absorption lines in their optical spectra generated from outflows with velocities of up to 0.2 c. In this work, we present the results of a multi-frequency study of a well-defined radio-loud BAL QSO sample, and a comparison sample of radio-loud non-BAL QSOs, both selected from the Sloan Digital Sky Survey (SDSS). Aims. We aim to test which of the cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
87
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 40 publications
(100 citation statements)
references
References 46 publications
12
87
1
Order By: Relevance
“…The bipolar wind model proposed by Punsly (1999a,b) was used by Ghosh & Punsly (2007) to explain the polar BAL QSOs found by Zhou et al (2006): in this model the BAL outflow would be aligned with the polar axis, while the relativistic jet would be nested inside of it. Recent works, based on large samples, do not confirm a young age for all BAL QSOs, but also a variety of orientations have been found (Bruni et al 2012;DiPompeo et al 2011). Also, on the arcsec-scale the majority of these sources remain unresolved in the radio band, with only about 10% or less showing an extended morphology (Bruni et al 2012;DiPompeo et al 2011).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The bipolar wind model proposed by Punsly (1999a,b) was used by Ghosh & Punsly (2007) to explain the polar BAL QSOs found by Zhou et al (2006): in this model the BAL outflow would be aligned with the polar axis, while the relativistic jet would be nested inside of it. Recent works, based on large samples, do not confirm a young age for all BAL QSOs, but also a variety of orientations have been found (Bruni et al 2012;DiPompeo et al 2011). Also, on the arcsec-scale the majority of these sources remain unresolved in the radio band, with only about 10% or less showing an extended morphology (Bruni et al 2012;DiPompeo et al 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Recent works, based on large samples, do not confirm a young age for all BAL QSOs, but also a variety of orientations have been found (Bruni et al 2012;DiPompeo et al 2011). Also, on the arcsec-scale the majority of these sources remain unresolved in the radio band, with only about 10% or less showing an extended morphology (Bruni et al 2012;DiPompeo et al 2011).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…To refine the BAL classification and set it in line with our previous work, in 2013 we considered the objects' spectra from the latest version of the SDSS (DR9, Ahn et al 2012) and performed a proper calculation of the absorption index (AI), as defined in Bruni et al (2012). We used the classical definition by Hall et al (2002):…”
Section: Optically Bright Samplementioning
confidence: 99%
“…Becker et al (2000) first used the radio emission spectral index to derive the jet orientation of BAL QSOs, and noted that this can lie in wide range of possible angles. After these works, different authors presented detailed studies about larger samples of radio-loud BAL QSOs, from which they reported a variety of possible orientations for the outflow, but also a variety of possible morphologies and ages for the radio source (Montenegro-Montes et al 2008;DiPompeo et al 2011;Bruni et al 2012Bruni et al , 2013). This does not suggest a scenario that would be clearly referable to one of the proposed models.…”
Section: Introductionmentioning
confidence: 99%